2002
DOI: 10.1161/01.hyp.0000015612.73413.91
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Left Ventricular Mass in African American and European American Youth

Abstract: Abstract-Increased left ventricular mass has been established as a strong risk factor for cardiovascular morbidity and mortality. To evaluate growth of left ventricular mass from childhood into early adulthood and its possible sociodemographic, anthropometric, and hemodynamic moderators, individual growth curves across age of left ventricular mass were created for 687 African American and European American males and females with a maximum of 10 annual assessments (age, 8.2 to 27.5 years). African Americans and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 36 publications
2
54
2
Order By: Relevance
“…40,41 Apart from increased left ventricular mass in Africans, Li et al 44 indicated recently that African Americans have higher BP variability than European Americans, contradicting a small study performed in England (N¼26) that indicated no ethnic differences. 45 Li et al 44 argue that the higher BP variability values of Africans are consistent with the prognostic value of BP variability, and the higher incidence and mortality of cardiovascular disease in Africans.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…40,41 Apart from increased left ventricular mass in Africans, Li et al 44 indicated recently that African Americans have higher BP variability than European Americans, contradicting a small study performed in England (N¼26) that indicated no ethnic differences. 45 Li et al 44 argue that the higher BP variability values of Africans are consistent with the prognostic value of BP variability, and the higher incidence and mortality of cardiovascular disease in Africans.…”
Section: Discussionmentioning
confidence: 98%
“…41 Furthermore, Havranek et al 42 indicated that ECG left ventricular hypertrophy contributes more to the risk of cardiovascular mortality in African Americans than in Caucasians. They also suggested that left ventricular hypertrophy should be a target of therapy to reduce ethnic differences in cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Subject recruitment, evaluation and annualized attrition rate have been described previously. 11,15,16 The mean age of subjects at first visit was 11.0 years with a range of 3.9-23.9 years.…”
Section: Subjectsmentioning
confidence: 99%
“…12,31 Individual growth curves in adiposity are characterized by their intercept (or level) and slope (rate of change). As described in detail previously, 10 we modeled the effects of age, age 2 , 3 .…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation